Genotypic and Allelic Frequencies of Hereditary Cataract in the Italian Population of Australian Shepherd and Miniature American Shepherd Dogs - Maria Grazia De Iorio; Giulietta Minozzi; Sara Ghilardi; Stefano Frattini; Mara Bagardi; Paola Giuseppina Brambilla; Alessandra Paganelli; Maria Cristina Cozzi; Francesca Vecchi; Michele Polli (Animals, 2025)
Hereditary cataract is a progressive ocular disorder that is present also in Australian Shepherd and Miniature American Shepherd dogs, primarily caused by a mutation in the HSF4 gene. This study analyzed 233 Australian Shepherd dogs tested in Italy between 2020 and 2024 to evaluate genotypic and allelic frequencies of the main causative mutation. DNA samples were collected and tested, classifying individuals as homozygous wild-type, heterozygous, or homozygous mutant. The overall mutant allele frequency was 6.01%. Furthermore, a small subset of 13 Miniature American Shepherds was analyzed and genetic tests revealed that they were all homozygous wild type, suggesting no presence of the causative allele in this small sample. These findings confirm the importance of genetic testing in dog populations emphasizing the need for responsible selection practices to further minimize the disease’s impact.